Diversidade bacteriana de carnes dry-aged e wet-aged por sequenciamento de nova geração do gene 16s (rrna) : Bacterial diversity from dry-aged and wet-aged meat using new generation sequencing of 16s gene (rrna) - Matos, Luiz Gustavo de, 1994- (2021)
Orientador: Nathália Cristina Cirone Silva